2016
DOI: 10.1177/0735633116667359
|View full text |Cite
|
Sign up to set email alerts
|

Use of WhatsApp in Higher Education

Abstract: The aim of this study is to investigate the use of WhatsApp application in anonymous peer assessment in higher education. The mobile phone application WhatsApp was used as both an anonymous and nonanonymous peer assessment tool in a classroom environment. The participants of the study were the students of two classes (sophomores and juniors), half of which were assigned to the anonymous peer assessment group and the other half to the nonanonymous peer assessment group for each class. The members of the anonymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…tional use of WhatsApp have indicated that it has potential to support learning anytime and anywhere, increase interest and motivation, provide cooperation, enhance learning, improve the interaction among learners, and learner-teacher (Bouhnik & Deshen, 2014;Church & de Oliveira, 2013;Guler, 2017;Jafari & Chalak, 2016;Mistar & Embi, 2016;Plana et al, 2013;Rambe & Bere, 2013;Rambe & Chipunza, 2013;Smit, 2012). Accordingly, it seems possible to suggest that Facebook and WhatsApp, along with their potential to provide informal cooperative learning environment, both could be more dynamic and effective with the help of Internet and mobile devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…tional use of WhatsApp have indicated that it has potential to support learning anytime and anywhere, increase interest and motivation, provide cooperation, enhance learning, improve the interaction among learners, and learner-teacher (Bouhnik & Deshen, 2014;Church & de Oliveira, 2013;Guler, 2017;Jafari & Chalak, 2016;Mistar & Embi, 2016;Plana et al, 2013;Rambe & Bere, 2013;Rambe & Chipunza, 2013;Smit, 2012). Accordingly, it seems possible to suggest that Facebook and WhatsApp, along with their potential to provide informal cooperative learning environment, both could be more dynamic and effective with the help of Internet and mobile devices.…”
mentioning
confidence: 99%
“…These studies indicate that Facebook, effects of which have often been researched, has potential to increase social interaction, interest and motivation, support learning anytime and anywhere, provide cooperation, increase sense of belonging and commitment, success, teacher-student interaction, provide peer support and feedback, and enable sharing of material and information (e.g., Bosch, 2009;Cain & Policastri, 2011;Goodband, Solomon, Samuels, Lawson, & Bhakta, 2012;Irwin, Ball, Desbrow, & Leveritt, 2012;Junco, 2012;Lim & Richardson, 2016;Madge, Meek, Wellens, & Hooley, 2009;Mitchell, 2012;Muñoz & Towner, 2011;Sánchez, Cortijo, & Javed, 2014;Selwyn, 2009;Shih, 2011;Wang, Woo, Quek, Yang, & Liu, 2012;Yang, Wang, Woo, & Quek, 2011). The results of the studies on the educational use of WhatsApp have indicated that it has potential to support learning anytime and anywhere, increase interest and motivation, provide cooperation, enhance learning, improve the interaction among learners, and learner-teacher (Bouhnik & Deshen, 2014;Church & de Oliveira, 2013;Guler, 2017;Jafari & Chalak, 2016;Mistar & Embi, 2016;Plana et al, 2013;Rambe & Bere, 2013;Rambe & Chipunza, 2013;Smit, 2012). Accordingly, it seems possible to suggest that Facebook and WhatsApp, along with their potential to provide informal cooperative learning environment, both could be more dynamic and effective with the help of Internet and mobile devices.…”
mentioning
confidence: 99%
“…Media is something that can use to bring messages or information from sender to receiver so that it can stimulate students' thoughts, feelings, concerns, and interests in such a way that teaching and learning activities occur. (Güler, 2016). from question and answer test.…”
Section: Medanmentioning
confidence: 99%
“…Research on the use of WhatsApp (Raiman et al, 2017) shows that this application improves learning by using messages linked to images (Cetinkaya, 2017). Its advantages include allowing almost constant and continuous contact between the agents involved in the T-L processes (Bottentuit et al, 2016), encouraging collaborative work (Güler, 2017), and promoting individual assessment of students (Petitjean and Morel, 2017).…”
Section: Using Whatsapp In Educationmentioning
confidence: 99%